2021
DOI: 10.1021/acs.jpclett.1c00653
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Excited-State Localization in Cs2AgBiBr6 Double Perovskite

Abstract: Cs 2 AgBiBr 6 is a promising metal halide double perovskite offering the possibility of efficient photovoltaic devices based on lead-free materials. Here, we report on the evolution of photoexcited charge carriers in Cs 2 AgBiBr 6 using a combination of temperature-dependent photoluminescence, absorption and optical pump–terahertz probe spectroscopy. We observe rapid decays in terahertz photoconductivity transients that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

26
196
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 104 publications
(246 citation statements)
references
References 74 publications
26
196
1
Order By: Relevance
“…A characteristic and strong peak located at around 438 nm is observed and questions remain about the origin of this peak. [50] This sharp peak, which contributes more than 20% of the overall light absorption of Cs 2 AgBiBr 6 perovskite, has been assigned to either excitonic absorption, the chargetransfer-like transition between Ag and Bi/Br orbitals, or localized Bi 6s-6p transitions. Recently, this characteristic absorption peak has been demonstrated to show no strong dependence on Cs 2 AgBiBr 6 nanocrystal sizes, as shown in Figure 2b, reflecting that the peak does not in fact originate from confined excitons.…”
Section: Photophysics Of Absorption and Photoluminescencementioning
confidence: 99%
See 1 more Smart Citation
“…A characteristic and strong peak located at around 438 nm is observed and questions remain about the origin of this peak. [50] This sharp peak, which contributes more than 20% of the overall light absorption of Cs 2 AgBiBr 6 perovskite, has been assigned to either excitonic absorption, the chargetransfer-like transition between Ag and Bi/Br orbitals, or localized Bi 6s-6p transitions. Recently, this characteristic absorption peak has been demonstrated to show no strong dependence on Cs 2 AgBiBr 6 nanocrystal sizes, as shown in Figure 2b, reflecting that the peak does not in fact originate from confined excitons.…”
Section: Photophysics Of Absorption and Photoluminescencementioning
confidence: 99%
“…[38,52,55] Note that there are reports claiming that the PL peak results from the spatially localized color centers which can be either intrinsic selftrapping of excitons/carriers or defects. [50,56] Instead, we have recently demonstrated that the PL emission of Cs 2 AgBiBr 6 is mainly from the band-to-band emission. To start, the fluencedependent PL intensity versus carrier density is measured and reveals a power-law factor of 1.94 and 1.26 when the excitation density is smaller or larger than 10 16 cm -3 , respectively, which implies both free carrier and exciton emission in Cs 2 AgBiBr 6 samples.…”
Section: Photophysics Of Absorption and Photoluminescencementioning
confidence: 99%
“…However, temperature-activated delocalization results in appreciable carrier mobilities at room temperature. 20,21 Moreover, mobile carriers were observed for microseconds after photoexcitation at elevated temperatures, 20 highlighting CABB as a potential alternative for leadhalide analogs.…”
mentioning
confidence: 99%
“…1 ps À1 to be intrinsic to CABB. 21 Such fast localization rates would be detrimental to its application in optoelectronic devices. However, temperature-activated delocalization results in appreciable carrier mobilities at room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation